2019
DOI: 10.1016/j.trb.2019.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Blue phase: Optimal network traffic control for legacy and autonomous vehicles

Abstract: With the forecasted emergence of autonomous vehicles in urban traffic networks, new control policies are needed to leverage their potential for reducing congestion. While several efforts have studied the fully autonomous traffic control problem, there is a lack of models addressing the more imminent transitional stage wherein legacy and autonomous vehicles share the urban infrastructure. We address this gap by introducing a new policy for stochastic network traffic control involving both classes of vehicles. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Levin et al ( 23 ) gave an MP control with AIM and dynamic lane reversal capable controller with proof of stability and showed significant performance improvement compared with first-come-first-served control. Rey and Levin ( 24 ) developed a new traffic network control policy based on an MP algorithm for CAVs, and they also gave a proof of stability. Yen et al ( 25 ) compared the fairness and vulnerabilities against cyber-attacks of four different BP based controllers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Levin et al ( 23 ) gave an MP control with AIM and dynamic lane reversal capable controller with proof of stability and showed significant performance improvement compared with first-come-first-served control. Rey and Levin ( 24 ) developed a new traffic network control policy based on an MP algorithm for CAVs, and they also gave a proof of stability. Yen et al ( 25 ) compared the fairness and vulnerabilities against cyber-attacks of four different BP based controllers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In light of the work by [4] and [12], Taale et al [15] and Sun et al [6] tested both a time-slotted BP and a cyclic BP in their experiments, and interestingly, they found that the time-slotted BP works better than the cyclic BP in general. More recently, [16] proposed a BP that can accommodate both human-driven and autonomous vehicles.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…As shown in Figure 1, the detection time of the first vehicle and the time interval between the first vehicle and the subsequent vehicle n are taken as the analysis parameters, and the recursive formula is obtained as shown in equation (1). e vehicle detection time, the time interval between vehicles, and the number of vehicles constitute the main influencing variables for analysing the accuracy of vehicle link travel time estimation:…”
Section: Basic Travel Time Functionmentioning
confidence: 99%
“…e travel time is always one kind of quantitative indicators to analyse traffic network performance based on link travel time or route travel time. Even in the near future with the emergence of autonomous vehicles in urban traffic networks and the mixed flow, travel time plays an important role on solving autonomous traffic control problem such as the blue phase design [1]. In addition, travel time is one of the crucial factors affecting drivers' behaviour when they lead or follow vehicle platoon in the mixed flow with autonomous vehicles and human driven vehicles, and some works on the dedicated lane management consider the vehicle time factors such as headway to improve lane capacity [2].…”
Section: Introductionmentioning
confidence: 99%